ANALISIS SWOT DALAM STRATEGI PEMASARAN PADA USAHA JASA DEKORASI PERNIKAHAHAN KAYIS DECORATION - Thoharudin, Kayis; Mutiasari, Annisa Indah; Cahyani, Rusnandari Retno (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2026)
This study aims to analyze the marketing strategy of the wedding decoration service business “Kayis Decoration” using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. Kayis Decoration is a business engaged in event decoration services, particularly weddings, established in 2020 in Klaten, Central Java. Amid growing competition in the decoration industry, marketing strategy is a crucial element that must be carefully and effectively designed. SWOT analysis is applied to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that influence the business operation. The findings reveal that Kayis Decoration has strengths in flexible services, competitive pricing, and high-quality decorations. However, several weaknesses were identified, including the absence of a dedicated warehouse, lack of promotion, and unstructured financial recording. Business opportunities remain promising due to market demand and evolving trends, although challenges such as strong competition and consumer bargaining power must be anticipated. Based on the analysis, strategies were formulated such as strengthening digital promotion, improving service quality, developing partnerships, and enhancing internal management. These strategies are expected to support Kayis Decoration in becoming a professional, competitive, and sustainable decoration service provider.